Improved detection of air-filled lesions using computed tomography in dogs with recurrent spontaneous pneumothorax through reduction of pulmonary atelectasis via positive pressure ventilation - Toshima, Atsushi; Fulkerson, Caroline V.; Kagawa, Yumiko; Murakami, Masahiro (Frontiers in Veterinary Science, 2024)
Spontaneous pneumothorax in dogs is predominantly caused by the rupture of air-filled lesions, such as bullae or blebs. The efficacy of Computed Tomography (CT) in detecting these lesions has been deemed limited due to its reportedly low sensitivity. This retrospective, cross-sectional study investigates the utility of CT in eight dogs diagnosed with recurrent pneumothorax, all of which had surgical confirmation of the cause of the pneumothorax. Thoracic radiographs were obtained before and the day following the CT studies. Initially, a CT study was conducted without positive pressure ventilation (pre-PPV CT). Subsequent CT studies were performed post-evacuation of pneumothorax and with positive pressure ventilation of 15 cmH2O until lung atelectasis was resolved (post-PPV CT). The pre-PPV CT and post-PPV CT images were anonymized and reviewed by two board-certified radiologists. The presence and morphology of air-filled lesions were evaluated on all images. Surgical findings were recorded and compared to the CT findings. Air-filled lesions were detected in 5 out of 8 dogs in the pre-PPV CT studies and in all 8 dogs in the post-PPV CT studies. The CT findings of air-filled lesions were consistent with surgical findings. None of the dogs showed increased severity of pneumothorax in radiographs taken the day following the CT studies. The study concludes that the resolution of lung atelectasis by evacuation of pneumothorax and positive pressure ventilation during CT studies is feasible and enhances the detection of air-filled lesions in dogs with recurrent spontaneous pneumothorax. This could potentially aid in improving surgical planning.